Subject-oriented method of building relationships between software metrics - Дишлевий, О.П. (Proceedings of National Aviation University (archive), 2009)
The article is dedicated to designing of a subject-oriented method of making dependences between software metrics. Existing environments for making dependences are reviewed, and the conclusion about need for development of special environment for making dependences between software metrics is made. Article describes the experiments which defined specifics of a method, offers its scheme, and defined special features of the method.